An Interleukin-6 Receptor Antibody Suppresses Atherosclerosis in Atherogenic Mice - Akita, Koji; Isoda, Kikuo; Sato-Okabayashi, Yayoi; Kadoguchi, Tomoyasu; Kitamura, Kenichi; Ohtomo, Fumie; Shimada, Kazunori; Daida, Hiroyuki (Frontiers in Cardiovascular Medicine, 2017)
IκBNS is a nuclear IκB protein which negatively regulates nuclear factor-κB activity. We demonstrated that IκBNS deficiency accelerates atherosclerosis in LDL receptor-deficient (LDLr−/−) mice via increased interleukin (IL)-6 production by macrophages. Previous studies showed that the increase in IL-6 might contribute to the development of atherosclerotic lesions. However, whether an anti-mouse IL-6 receptor antibody (MR16-1) can protect atherosclerotic lesions in atherogenic mice remains to be elucidated. We investigated atherosclerotic lesions in LDLr−/− and IκBNS−/−/LDLr−/− mice after 16 weeks consumption of a high-fat diet. All mice received intraperitoneal injections of MR16-1 or phosphate-buffered saline (PBS) (control) once a week during a high-fat diet consumption. Treatment of MR16-1 yielded no adverse systemic effects, and we detected no significant differences in serum cholesterol levels in either group. The atherosclerotic lesions were significantly increased in IκBNS−/−/LDLr−/− compared with LDLr−/− mice (p < 0.01) under treatment of PBS. However, MR16-1 treatment abolished the significant difference of atherosclerotic lesions between IκBNS−/−/LDLr−/− and LDLr−/− mice. Interestingly, MR16-1 also significantly decreased atherosclerotic lesions in LDLr−/− mice compared with PBS treatment (p < 0.05). Immunostaining revealed percent phospho-STAT3-positive cell were significantly decreased in the atherosclerotic lesions of MR16-1 treated both IκBNS−/−/LDLr−/− and LDLr−/− mice compared with PBS-treated mice, indicating MR16-1 could suppress atherosclerotic lesions via the inhibition of IL-6–STAT3 signaling pathway. This study highlights the potential therapeutic benefit of anti-IL-6 therapy in preventing atherogenesis induced by dyslipidemia and/or inflammation.